2022
DOI: 10.21037/atm-22-4303
|View full text |Cite
|
Sign up to set email alerts
|

Exploring biomarkers and transcriptional factors in type 2 diabetes by comprehensive bioinformatics analysis on RNA-Seq and scRNA-Seq data

Abstract: Background: Type 2 diabetes (T2D) is a prevalent chronic disease with elusive. Combining transcriptome and single-cell sequencing data to explore biomarkers of T2D could provide new insights into the in-depth understanding of the molecular mechanisms and diagnosis of T2D. Methods:The GSE41762 dataset including RNA-seq data for healthy and T2D patients, was obtained from the Gene Expression Omnibus (GEO) database. The potential functions of the differentially expressed genes (DEGs) were revealed by Gene Ontolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The role of islet cell types in the genetic signalling pathways associated with T2DM susceptibility, particularly islet beta cell specificity, was identified by Rai V et al [11][12]. Huang Y et al identified six islet cell types and reported that SLC2A2, serinf1, RASGRP1 and CHL1 are biomarkers of T2DM; their analysis provided new markers for clinical diagnosis [13]. The 1 million cell atlas constructed by Wu H et al reveals the types of kidney cells involved in the development of diabetic kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…The role of islet cell types in the genetic signalling pathways associated with T2DM susceptibility, particularly islet beta cell specificity, was identified by Rai V et al [11][12]. Huang Y et al identified six islet cell types and reported that SLC2A2, serinf1, RASGRP1 and CHL1 are biomarkers of T2DM; their analysis provided new markers for clinical diagnosis [13]. The 1 million cell atlas constructed by Wu H et al reveals the types of kidney cells involved in the development of diabetic kidney disease.…”
Section: Introductionmentioning
confidence: 99%